2009
DOI: 10.1590/s0103-50532009000700015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage induced by S(IV) in the presence of Cu(II) and Cu(I) complexes

Abstract: CuII G3 ∼ CuII GGA. Specifically for CuII BCA the damage occurred even at lower S(IV) concentration (0.1 µmol L-1). For the Cu(II) complexes with glycylglycylhistidine, glycylhistidylglycine, glycylhistidyllysine and glycylglycyltyrosylarginine the Cu(III) formation and the DNA damage was not observed.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…For this purpose, we have investigated the effect on oxygen-derived radical formation of Cu(II) complexed with four different stable imine ligands [41][42][43], cycling the metal between the 2+ and 1+ redox states, and with three low molecular weight peptide ligands known to form stable Cu (III) complexes in solution [44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we have investigated the effect on oxygen-derived radical formation of Cu(II) complexed with four different stable imine ligands [41][42][43], cycling the metal between the 2+ and 1+ redox states, and with three low molecular weight peptide ligands known to form stable Cu (III) complexes in solution [44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…Condensation of the amine ligands 1,3-diaminepropane (pn), ethylenediamine (en), 2-aminoethyl pyridine (epy) or 8-aminoquinoline (amiquin) with isatin (isa), followed by metallation with Cu(II) perchlorate, yielded the Cu(II)-isatin-diimine complexes [Cu(isa-pn)] The structures of the complexes were confirmed by comparison of their UV-VIS and EPR spectra with published data for these compounds [44][45][46][47]. Both classes of complexes showed to be structurally stable in aqueous solutions at all conditions used in experiments.…”
Section: Chemicalsmentioning
confidence: 99%
“…In addition to ROS production, DNA damage has been previously observed in cells that were treated with sulfite (Hayatsu and Miller, 1972;Shi and Mao, 1994). In a recent study, Alipazaga et al (2009) reported that oxidative DNA damage was induced by (bi)sulfite solutions in the presence of Cu(II) peptide complexes. This result provided more data in support of the DNA damaging effects of sulfite exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these effects, sulfites were also found to be mutagens, which may be related to tumor occurrence. Alipazaga et al (2009) reported that exposure to (bi)sulfite solution can cause oxidative DNA damage when in the presence of Cu(II) peptide complexes. Zeiger (1993) also reported that sulfites can cause DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that sulfite toxicity is due to the increased production of ROS in the mitochondria and inactivation of mitochondrial proteins [9]. Studies have also shown that sulfite radical is capable of damaging DNA/ RNA, lipids, and proteins [51,76,77,[95][96][97]. The increased production of oxidants can damage the mitochondrial proteins, lipids, DNA/RNA and this is implicated in several neurological diseases [86,91,98].…”
Section: Discussionmentioning
confidence: 99%